Бүгінгі дарын иесі-ертеңгі егеменді еліміздің тірегі - Бекетаева, С.К. (My University, 2013)
This report examines ways to develop children's abilities, made a theoretical analysis. The report also contains data research and education capabilities of Soviet foreign psychologists. The report gives particular talent training and types of abilities.